Sociologia histórica crítica: o neoliberalismo na América Latina e Brasil do século XXI - Almeida, José Eustáquio Leandro Assis Cavalcanti Albuquerque de (2019)
This thesis / dissertation aims to analyze critical Latin American and Brazilian historical sociology on the neoliberal capitalist program. It is about being a type of historicity about this system of thought, its practical application of state, specificity and territories, ideological cleavages, super-exploitation as a new modality of more value in the international division of labor, privatizations, normativity of an ethos and interests of the bourgeois elite or class, a new phase of capital accumulation in the 21st century. Therefore, it is an analysis of the concrete experiences of the class struggle through which this program was carried out and institutionalized by the State. From Western Europe to Latin America and Brazil. Dependent process or interdependente political economic with U.S.A., global hegemony. The loss of sovereignty, deindustrialization and crisis of Brazilian national identity, technological backwardness and cultural obscurantism.